Community engagement in pastoralist areas: Lessons from the public dialogue process for a new refugee settlement in Turkana, Kenya - Cory Rodgers (SpringerOpen, 2021)
Abstract Large-scale development interventions have long failed to accommodate the needs and preferences of pastoralists or the systems of resource governance and land tenure upon which they rely. However, advocates of rights-based approaches to development emphasise the importance of community participation in planning and agenda-setting, and in Kenya, public participation is a formal constitutional requirement for government decision-making processes. In 2015, the United Nations High Commissioner for Refugees concluded negotiations with local stakeholders about the use of 15 km2 of communal rangelands to build a new refugee settlement in Turkana County, Kenya. Negotiations entailed a community dialogue process involving local people living in the vicinity of the proposed settlement. This paper retrospectively examines the inclusivity of the dialogue process, with particular attention to the involvement of pastoralists and the representation of their interests. Interviews and focus groups conducted with a range of key informants and community stakeholders highlighted two key problems. First, negotiations relied upon a simplistic approach to communal land tenure that overlooked the complexity of overlapping and often contested access rights. Second, there was an over-reliance on urban professionals and politicians as intermediaries between rural communities and development actors. Even where elite intermediaries act in good faith, they may introduce an ‘oppidan bias’ into development policies, thereby marginalising the viewpoints of non-urban, non-sedentary demographics, such as pastoralists. I conclude with recommendations for the UNHCR to develop a more explicit strategy for direct engagement with host community stakeholders in Turkana and with increased attention to the interests of livestock producers and the nuances of pastoralist land use.